2016
DOI: 10.1039/c5sm02310f
|View full text |Cite
|
Sign up to set email alerts
|

Micro-mechanics of electrostatically stabilized suspensions of cellulose nanofibrils under steady state shear flow

Abstract: In this study, we characterized and modeled the rheology of TEMPO-oxidized cellulose nanofibril (NFC) aqueous suspensions with electrostatically stabilized and unflocculated nanofibrous structures. These colloidal suspensions of slender and wavy nanofibers exhibited a yield stress and a shear thinning behavior at low and high shear rates, respectively. Both the shear yield stress and the consistency of these suspensions were power-law functions of the NFC volume fraction. We developed an original multiscale mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 73 publications
3
36
1
Order By: Relevance
“…The solid-like properties of nanocellulose suspensions can also be observed from steady-state flow curves (e.g., Figure 4b). As shown in Figure 4b, CNF suspensions exhibit a macroscale yield stress at low strain-rates [100,[104][105][106]. This regime is then followed by a shear-thinning behaviour, where the suspension viscosity decreases with increasing the strain-rates [107].…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…The solid-like properties of nanocellulose suspensions can also be observed from steady-state flow curves (e.g., Figure 4b). As shown in Figure 4b, CNF suspensions exhibit a macroscale yield stress at low strain-rates [100,[104][105][106]. This regime is then followed by a shear-thinning behaviour, where the suspension viscosity decreases with increasing the strain-rates [107].…”
mentioning
confidence: 89%
“…To be printable in a 3D printer, the fluid needs to flow in the printer and have the ability to become like a "solid" on a substrate after being dispensed (Figure 8b) [130]. As mentioned in Section 3.1, nanocellulose suspensions are yield stress fluids that are characterised by a pronounced shear thinning behaviour at high strain-rates [100,107]. Hence, these suspensions are particularly suitable for this type of processing route.…”
Section: Extrusion Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that aqueous dispersions of slender and kinked CNFs display non-Newtonian rheological behavior characterized by shear thinning and pronounced viscoelastic behavior at concentrations above the gelation threshold (de Kort et al 2016;Jowkarderis and van de Ven 2015;Martoia et al 2016). Recent studies have investigated the effects of pulp source (Tanaka et al 2016), fibril dimension and concentration (Agoda-Tandjawa et al 2010), mechanical treatments (Pääkkö et al 2007), ionic strength (Dong et al 2013), pH (Fall et al 2013), as well as addition of amphiphilic molecules (Quennouz et al 2016) on the rheology of CNF dispersions.…”
Section: Introductionmentioning
confidence: 99%